Arthur Lumsden interviewed by Peter Parkhill for the Peter Parkhill collection - Lumsden, Arthur; Parkhill, Peter (1993)
Folkloric recording.
Digital master available
Keywords: Lumsden, Arthur -- Interviews; Collectors and collecting -- Australia; Engineers -- Australia; Folk music -- Australia; Engineers